THE ROLE OF TRANSFORMATIONAL LEADERSHIP IN IMPROVING MANAGERIAL PERFORMANCE THROUGH ORGANIZATIONAL COMMITMENT ON NATIONAL STRATEGIC PROJECTS - Sudibyo Aji Narendra Buwana; Rahayu Puji Suci; Adya Hermawati (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
This study aims to test and prove empirically the influence of transformational leadership on managerial performance through organizational commitment to national strategic projects in Kolaka Regency, South East Sulawesi. Theoretically, the results of this research are expected to enrich and complement the body of knowledge in the field of human resource management so that it can be useful for academics and practitioners. This research is explanatory research that examines and explains the research variables in a cross-sectional manner. The quantitative approach is used as the main analytical method, supported by a qualitative approach. The research population is employees who occupy the positions of first-line managers, middle managers, and top managers in the national strategic project area. The research sample consisted of 68 respondents using proportional random sampling and was analyzed using structural equation modeling (partial least squares) (SEM) with SmartPLS software. The results of this study indicate that transformational leadership has no role in improving managerial performance; transformational leadership plays a role in increasing organizational commitment; organizational commitment plays a role in improving managerial performance; and transformational leadership mediated by organizational commitment has no role in improving managerial performance. Keywords: Transformational Leadership, Organizational Commitment, Managerial Performance